Application Of E-Module and Video Tutorials to Student Learning Motivation and Learning Effectiveness In Physical Education, Sports, And Health - Anung Priambodo; Dwi Cahyo Kartiko; Muchamad Arif Al Ardha; Mohammad Fathur Rohman (STKIP Muhammadiyah Kuningan, 2023)
This study aims to develop an online and offline-based small ball learning electronic module to perfect the PJOK learning design needed today. The subjects of this study were junior high school (SMP) PJOK teachers in the Surabaya area. The research method used is mixed methods. The research phase consists of designing a training model, selecting samples purposively, conducting training, facilitating the development of small-ball electronic modules, monitoring the implementation of training products, and assessing student motivation. The results of this study can help PJOK SMP teachers improve their competence in digital literacy so that the quality of their learning becomes more improved, not only practical but also efficient and exciting. 21 junior high school PJOK teachers and 58 junior high school students were involved in this study. 100% of teachers said they needed training in developing e-modules and video tutorials for physical education learning. The 21 PJOK teachers who participated in the movement gave an excellent assessment of the activity carried out and have been able to develop an electronic module complete with video tutorials. 99.9% of students stated that they were very motivated in learning and involved in PJOK learning after using the electronic module from the teacher.